Macro/micro simultaneous validation for multiscale analysis of semi-periodically perforated plate using full-field strain measurement. (May 2016) - Matsuda, T.; Ito, T.; Akimoto, S.; Kobori, H.; Goto, K.; Takano, N.
Abstract: Multiscale analysis of a semi-periodically perforated plate based on a homogenization theory is experimentally validated both macroscopically and microscopically, using a full-field strain measurement. To do this, a plate-fin-type perforated plate with a misaligned microstructure is considered as a semi-periodically perforated plate. Then, a homogenization theory that can analyze macroscopic behavior and microscopic stress and strain distributions of the perforated plate is presented. To validate the theory, a tensile test of a plate-fin-type semi-periodically perforated plate made of epoxy resin is conducted. During the test, the microscopic deformation of the specimen is observed with a digital image correlation (DIC) full-field measurement system, from which microscopic strain distribution of the specimen is calculated. It is shown that the obtained strain distribution satisfies the unit-cell periodicity except at edges of the periodic structure, and that the strain distribution is in good agreement with the result of analysis using the homogenization theory. It is also shown that the macroscopic stress–strain relationships obtained by the experiment and analysis agree well, supporting the macroscopic and microscopic validity of the multiscale analysis using the homogenization theory. Highlights: Multiscale analysis is experimentally validated macroscopically and microscopically. A tensile test of a plate-fin-type semi-periodically perforated plate is conducted. Microscopic strain distribution is observed with a DIC full-field measurement system. Multiscale analysis for the plate is performed based on a homogenization theory. Results of the experiment and analysis agree well in both macro- and micro-scales.